Causes, Effects and Potential Health Risk of Gully Erosion Menace in Calabar Municipal: Residence Perspective - Bassey, Bassey (International Journal of Environmental Sciences, 2023)
Purpose: The present study sought to investigate the potential health risk associated with gully erosion in addition to environment effect which is commonly investigated upon by researchers. The prevalence of gullies in Calabar Municipal was also a unique factor in this study. Methodology: Data were gathered from both primary and secondary sources. The main instrument for gathering primary data was the questionnaire design by the researcher and validated with a reliability coefficient of .76. Descriptive statistics of mean, and graphs were used to answer the research questions while the hypotheses were tested using dependent t-test at .05 level of significant. Findings: The findings revealed that human activities such as farming, intensive and short-period rainfall, improper land use, improper irrigation design, improper discharge of water in the channels¸ soil characteristics where the cause of gully erosion in the study area; while open grassing was not part of the cause of gully erosion in the study area. it was further discovered that effect of gully erosion included, Loss of farmland, threat to vegetations and biodiversity, loss of properties, increase poverty and famine, expansion of degraded land, increase surface runoff, low agricultural production, environmental destruction with significant health implication p<.00<.05. Unique Contribution to Theory, Practice and Policy: The study concluded that there is need for adequate funding, committed political will (not lip-service) and well-articulated sustainable policies are required in other to solve the problems of gully erosion in Calabar municipal.